Awareness And Practices Regarding Menstrual Hygiene Among Women of Reproductive Age Group Attending a Tertiary Care Hospital of Indore, India - Gupta, Mayank; Tiwari, Sonia; Wavare, R R (National Journal of Community Medicine, 2015)
Background: There is a substantial lacuna in the knowledge about menstruation among adolescent girls and women of reproductive age group. Objective of the study was to assess the knowledge amongst women of reproductive age group regarding menstrua- tion and its hygiene related practices. Methods: All females of reproductive age group (15-45 years) attending gynaecology OPD in the month of January 2015 at Au- robindo hospital was administered a pretested semi-structured questionnaire regarding knowledge and practices related to men- strual hygiene. Results: The mean age of females 30.7 years while 13.2 ±0.75 years, was mean age of menarche. The first source of information regarding menarche came from their mothers as 36.5% were only aware of menstruation before menarche. During menstruation 67.7% used sanitary pads while rest used cloths. The cleaning of external genitalia daily was practiced by 90.3% of urban living participants where in those living in rural areas were 83.09%. Conclusion: Literacy status was found to be significant for awareness about menstruation and the use of sanitary pads. Sig- nificant difference was also found in the use of sanitary pad vs cloth in those living in rural and urban areas.